Der japanische Botschafter und seine Gattin bei ihrer Ankunft in Berlin. Rechts von Bülow-Schwanten
Der japanische Botschafter und seine Gattin bei ihrer Ankunft in Berlin. Rechts von Bülow-Schwanten.